A imagem entre vinculações e interpretações: consumo, mídia e estetização pelas lentes da comunicação e da iconologia - Portugal, Daniel Bittencourt (2010)
This work approaches the image from the interface between Communication (Media studies) and Iconology. At this border, stands out not the image as an independent object, not the understanding of the image exclusively from men’s perspective, but the relationships between men and images. To study those relationships, it proposes an analytic division between a bonding dimension, based on sensible and affective forms of connection, and an interpretation dimension, more related to forms of constructing perceptual images and to the visual interpretation of them. The main focus of the research is the contemporary dynamics of image consumption, marked, as we argue, by the imbrications of three logics: “mediatic”, “of consumption” and “of aesthetization”. We consider especially relevant to the understanding of those dynamics the incorporation of a historical approach able to scrutiny a myriad of events, temporally close or distant, in which the image played a central role canalizing social tensions.